Salivary Gland Tumors in Libyan Population: A 20- Years Retrospective Study of 60 Cases - Mansora Hamad; Salwa Ahmeida; Samar Hamed; Jamila Issawi (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objectives. Salivary gland tumors (SGT) are relatively uncommon. They pose considerable challenging in diagnosis because their histopathological features and behavior diversity. There are several epidemiological studies describe their incidence and frequency. The current study aims to investigate the diverse histological types and distribution clinical characters. It also aims to compare our result with similar studies in different population to draw general profile of salivary gland tumors in Benghazi. Methods. A retrospective study was carried out in oral diagnosis, oral medicine, oral pathology and radiology department of faculty of dentistry at Benghazi university from 2000 to 2019. Information gathered was the year of diagnosis, age, gender, site, symptoms and histopathological diagnosis. The data collected was analyzed with SSPS. Result. Of the total 60 salivary gland tumors, 25 (41.7%) was benign tumors in which the pleomorphic adenoma was the most common type (n=24, 96%) and malignant tumors account 35(38.3%) with mucoepidermoid carcinoma is the most frequent (n=41, 40%). Female: Male ratio 1.3:1 with average age of 40.5 (range 11-94). 91.1% of salivary gland tumors were diagnosed in minor salivary gland where most of cases occurred in palate by 8.9%. major salivary glands were affected by 8.9% mostly in parotid gland (7.2%). Almost of cases were diagnosed as painless swelling. Conclusion: The malignant salivary gland tumors more common the benign type with the palate is the principle anatomical location. Pleomorphic adenoma is the most common pathological finding with predominance of female over male.